Sex and gender in acute care medicine - McGregor, Alyson J.; Choo, Esther K.; Becker, Bruce M. (New York, NY : Cambridge University Press, 2016)
"Until the last decade, clinicians and researchers assumed that the medical evaluation and treatment of both women and men were the same. This archaic and dangerous notion persisted in spite of the clear anatomic and physiologic differences between the genders. Today, we fully understand that this paradigm is false. In all specialties of medicine, practitioners and researchers are beginning to consider the influence of sex and gender and how it should inform the care of their patients. This book focuses on the issue of sex and gender in the evaluation and treatment of patients specifically in the delivery of acute medical care. It serves as a guide both to clinicians interested in the impact of sex and gender on their practice and to researchers interested in the current state of the art in the field and critical future research directions"--
Includes bibliographical references and index.
Keywords: Emergency Treatment; Sex Factors; Acute Disease -- therapy; Diagnosis, Differential; Symptom Assessment; Print books